Balancing Decentralization for Restoration in Power Distribution Systems With Agents - Venturini, Lucas F.; Baracy, Yago L.; Silva, Rodrigo V. P. C.; De Freitas, Bruna K.; Dos Santos, Erika P.; Branco, Nilton O.; Monteiro, Marcos E. P.; Hubner, Jomi F.; Issicaba, Diego (IEEE access, 2022)
Power distribution systems are subject to faults that may cause service interruptions. The outage impact can be attenuated by restoration procedures, aiming to reconfigure the grid until faulted components are repaired. Proposals for these procedures are usually either fully centralized or fully decentralized. In this paper, a hybrid approach (partially decentralized) for the restoration problem based on a multi-agent system (MAS) is proposed and evaluated. Results show that caution must be taken when specifying the level of decentralization achieved by agent based procedures devoted to system restoration, especially if low power devices are utilized to achieve agent communication.